Water quality characteristics of municipal wastewater treatment plants and the prospect of reclaimed water utilization in lower-middle income and water-scarce areas: A case study of Puyang - Yutong Duan; Hongbo Xi; Zhikai Qin; Ruili Guo; Fang Wang; Yue Yuan (Water Cycle)
Water scarcity is a key bottleneck for China's economic and social development. Reclaimed water presents a sustainable solution, but its utilization remains limited, especially in lower-middle income cities like Puyang. This study investigates the potential for reclaimed water utilization in Puyang, a key industrial hub in the Central Plains Economic Zone facing severe water shortages. Operational data from 20 municipal wastewater treatment plants (WWTPs) in 2023 were analyzed to assess water quality parameters, treatment efficiencies, and hydraulic load rates. Results indicate the seasonal variation in hydraulic load rates, probably affected by heavy rainfall during the rainy season, which posed operational challenges for WWTPs. Influent water quality analysis showed high concentrations of COD, NH₃-N, TN, and TP, and nutrient ratios that often exceeded the optimal level for biological nutrient removal. Effluent water quality generally met the discharge standards, though TN removal efficiency was unsatisfactory in some cases. The study also explored the future potential of reclaimed water in Puyang, highlighting opportunities to increase utilization rates to 30% by 2025 through enhanced infrastructure and technological innovations. Environmental assessments confirmed that treated water met industrial and landscape irrigation standards, while social and economic analyses showed that cost-effective water reuse offered advantages over other unconventional water sources. However, challenges such as inadequate regulatory frameworks, limited infrastructure and the need for systematic planning have hampered progress. This study provides a comprehensive evaluation of reclaimed water utilization in Puyang, offering valuable insights for sustainable water resource management in similar regions.